Sosialisasi Dan Pendampingan Sertifikasi Halal Bagi Dapur Satuan Pelayanan Pemenuhan Gizi (SPPG) Di Kabupaten Rokan Hulu - Nilam Erman; Merry Meilany (Journal of Community Sustainability, 2026)
The Free Nutritious Meal Program (MBG) through the Nutrition Fulfillment Service Unit Kitchen (SPPG) requires the implementation of the Halal Product Assurance System (SJPH) as a form of compliance with Halal Product Assurance regulations while ensuring the safety, quality, and halalness of food served to the public. However, some SPPG managers still have limited understanding of the requirements, procedures, and stages of applying for halal certification. This community service activity aims to improve the knowledge, skills, and readiness of SPPG managers in implementing SJPH and preparing for the halal certification process. The implementation methods include socialization, training, interactive discussions, assistance in preparing SJPH documents, and evaluation using pre- and post-tests for 50 participants from four SPPG Kitchens in Rokan Hulu Regency. The results of the activity showed an increase in participants' understanding of halal regulations, SJPH implementation, and halal certification mechanisms. All partner kitchens successfully compiled basic SJPH documents and were declared ready to continue the halal certification application process in accordance with applicable regulations.